Association Between the Neutrophil-to-Lymphocyte Ratio and the Degree of Carotid Artery Stenosis - Ari Bandana Tasrif; Subandi Subandi (Jurnal Ners, 2026)
Ischemic stroke accounts for the majority of instances and is mostly linked to carotid artery stenosis brought on by inflammatory atherosclerosis. This study used medical record data of hospitalized ischemic stroke patients who had digital subtraction angiography (DSA) between January and August 2025. It was an analytical observational study with a cross-sectional design that was carried out at Dr. Moewardi Hospital in Surakarta from October to November 2025. Purposive sampling was used to choose samples based on inclusion and exclusion criteria; the North American Symptomatic Carotid Endarterectomy Trial (NASCET) criteria were used to determine the degree of carotid stenosis; SPSS version 25 was used for statistical analysis using Pearson or Spearman correlation tests based on data distribution. Most ischemic stroke patients were male, aged 50–64 years, with diabetes mellitus and hypertension as the main comorbidities, and the majority had mild to severe carotid stenosis, while a small proportion had critical stenosis or total occlusion. While sex, age, hypertension, diabetes mellitus, and dyslipidemia did not substantially correlate with the degree of carotid artery stenosis (p above 0.05), NLR was the only predictor that did (p below 0.001). NLR was the only independent predictor that was substantially correlated with the degree of carotid artery stenosis, according to multivariate analysis using ordinal logistic regression (B was 0.227; p was 0.012). In ischemic stroke patients at Dr. Moewardi Hospital in Surakarta, NLR is substantially correlated with and an independent predictor of the degree of carotid artery stenosis.